Meet the lithographer - Bazin, Gaby (David Zwirner Books, 2023)
Combining science, art, and history, Meet the Lithographer showcases a centuries-old printing practice that evolved into the process used today to print books, magazines, newspapers, and posters. This enchanting behind-the-scenes tour of the lithographer's workshop offers an inside look at the tools, techniques, and stories that define lithography.